2005
DOI: 10.1108/10610420510609285
|View full text |Cite
|
Sign up to set email alerts
|

Risk and maximum acceptable discount levels

Abstract: Purpose -Studies on optimal discount levels have sometimes yielded contradictory results, leaving practitioners with unclear direction. This paper proposes clarifying the optimum discount levels. Design/methodology/approach -This study asked 453 consumers to choose their own optimal discount levels (from 0-80 percent) for eight product categories across two distribution channels (physical store and online merchant). Then they were asked if the reason if they did not always select the deepest discount. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
(28 reference statements)
2
28
0
Order By: Relevance
“…Our fi ndings also support the view that, although there is a positive relationship between the fi rst-period price and the price discount, it is not realistic to continually increase regular prices and offer deeper discounts. These fi ndings are consistent with the empirical evidence that deep discounting in some product categories negatively infl uences consumer perceptions and might decrease the probability of purchasing in both the short and the longterms (Drozdenko & Jensen, 2005;Gupta & Cooper, 1992;Marshall & Leng, 2002).…”
Section: Scholarly Contributionssupporting
confidence: 90%
“…Our fi ndings also support the view that, although there is a positive relationship between the fi rst-period price and the price discount, it is not realistic to continually increase regular prices and offer deeper discounts. These fi ndings are consistent with the empirical evidence that deep discounting in some product categories negatively infl uences consumer perceptions and might decrease the probability of purchasing in both the short and the longterms (Drozdenko & Jensen, 2005;Gupta & Cooper, 1992;Marshall & Leng, 2002).…”
Section: Scholarly Contributionssupporting
confidence: 90%
“…The effects of price discounts are often measurable, and because they are able to increase the store traffics, they are able to support relationships between manufacturers and retailers, and ensuring that a particular brand is well stocked and has adequate shelf space in the retail stores (Gendall et al 2006;Liu et al 2015). Despite numerous studies on the influence of discount on product demands, results have shown inconsistent and contradictory outcomes on the effects of price discounts on product demands (Drozdenko and Jensen 2005). Marshall and Leng (2002), for example, found that although product sales increased when discount is being offered from 10 to 50%, additional increase between 60 and 70% has no effect on product sales.…”
Section: Discount Valuementioning
confidence: 96%
“…On the other hand, based on attribution theory, when information is being thoroughly processed, consumers are able to rely on attribute information besides price to evaluate a product's quality (Drozdenko and Jensen 2005). When purchasing products online, there are various information about the product, as well as online reviews which may result in customers viewing discount as a monetary gain, and may increase the intention to purchase the product.…”
Section: Discount Valuementioning
confidence: 99%
“…Furthermore, the quantitatively measurable nature of the price discounts effect enables vendors to guarantee the availability of their products to their consumers (ibid.). However, even though many studies have examined the influence of discount on product demands (Ehrenberg et al, 1994;McNeill, 2013), Drozdenko and Jensen (2005) have highlighted contradictions and inconsistencies on the effect of price discounts on product demands. A study by Gupta and Cooper (1992), for example, has suggested that a price discount threshold level of 15% is enough to encourage purchases of the product in the US.…”
Section: Discount Valuementioning
confidence: 99%
“…Suri et al (2000) and Marshall and Leng (2002) have noted that price information of a product may be used as a cue to determine its inherent perceived quality by customers. Attribution theory posits that consumers rely on price and other attributive information when processing information to come up with a final evaluation of the product's quality (Drozdenko and Jensen, 2005). This attributive information on the product may result in the customers' final evaluations of the product's discount as being perceived to be a monetary gain to them.…”
Section: Discount Valuementioning
confidence: 99%